Interplay of GM Crops and Consumers Rights: Reviewing Handling and Labelling Mechanism Under the Existing Biosafety Framework of India - Oishika Banerji (Law and Judicial Review, 2026)
Objective: The present study becomes the voice for consumer rights that needs attention and protection in the context of genetically modified crops (GM crops) in India. In doing so, the study considers consumers as the representative of public interest and a primary stakeholder of such crops. While consumers are made subjects of handling and production consequences of consumable GM crops, labelling of such transgenic products promotes consumers to exercise their ‘right to choose’ and make informed decisions in regards to it. The interplay of the three terms, namely, harm, difference and choice, witnesses a recurring appearance in the present literature. While ‘harm’ refers to the concerns that walk with GM crops, ‘difference’ visualizes the required distinction between GM and non-GM crops and lastly, ‘choice’ reflects consumers’ ability to make rational decisions with respect to GM crops. The present research questions whether the existing biosafety framework of India caters to consumer needs while carrying out the handling and labelling mechanism of GM crops. Research Design & Methods: The present study discusses handling and labelling of GM crops as both play a fundamental role in order to ensure food safety for consumers. In doing so the study adopts a doctrinal research method bringing in India's biosafety framework alongside international instruments adopted. To extend support to the deliberations made, a comparative study has been done as well by reflecting on the approaches of the US and EU in the present context. Findings: The study does not deny the competency that the current biosafety framework and statutory authorities in place have to regulate GM crops. But, absence of authoritative liability catalyzed with unbridled power eclipses consumer rights thereby hindering public confidence. Such hindrances become subject to judicial review as has been with GM Mustard by the Apex Court. Hence arises the need for indispensable reform. Contributions: India, being an executive committee member of the Codex Alimentarius Commission (CAC) and ‘supposedly’ adhering to it must be having in place an effective biosafety framework to take care of handling and labelling of GM crops. Interestingly enough, in all the three transgenic crop matters that India has been home to, fingers have been pointed towards authoritative decision-making. The underlying problem therefore gets addressed in this research thereby adding to the series of literatures that is numerically less in the present time. Novelty: This study uniquely centers consumer rights within GM crop regulation by highlighting overlooked regulatory loopholes and issues of authoritative decision-making in India’s biosafety framework.